Alborziphyllinae, A New Late Devonian Rugose Corals Subfamily - A.R Ashouri (Journal of Sciences, Islamic Republic of Iran)
Members of the family Laccophyllidae are small, solitary rugose corals with stratigraphic ranges from Silurian to Permian. Among the laccophyllids, axial ends of major septa are united in an aulos and dissepiments may be absent or present. Minor septa can be contratingent and sometimes are small or in some genera are absent. Septa and aulos may be thick or thin. In this study, Famennian rugose corals of the Khoshyeilagh Formation in the north of Meyghan village (35 km NE Shahrood, Eastern Alborz) have been investigated for the first time. All the studied corals share their common characteristics with family Laccophyllidae. Convincingly, based on comparison of the presence of some key features among the collected samples with characteristics of existed subfamilies of laccophyllids, establishing a new subfamily can be essential. The Alborziphyllinae (new subfamily) encompasses a Late Devonian laccophyllid lineage. The new subfamily described here includes a new genus, Alborziphyllum and two new species, Alborziphyllum ferdowsiense and Alborziphyllum lonsdaleiforme.